Prevalence and antimicrobial resistance of Salmonella spp. isolated from free-ranging wild boars in the State of São Paulo, Brazil - Carraro,Paulo Eduardo (2022)
ABSTRACT: European wild boars (Sus scrofa) are considered exotic invasive species worldwide. Invasions of wild boars are a growing public health concern, as wild boars may represent an important reservoir of zoonotic pathogens, including bacteria of the genus Salmonella. The aim of this study was to determine the prevalence and serovars of Salmonella spp. in free-ranging wild boars legally hunted in the state of São Paulo, Brazil, and the susceptibility of those Salmonella spp. to antimicrobials. Fecal samples and mesenteric lymph nodes were acquired from 63 wild boars. The prevalence of Salmonella spp. in free-ranging wild boars was 9.5 % (6/63; confidence interval: 4.4 % - 19.2 %). Six serovars were isolated: S. enterica subsp. enterica ser. 4,5,12:-:1,2, S. enterica ser. Cerro, S. enterica ser. Madelia, S. enterica ser. Typhimurium, S. enterica ser. I (4,5,12:i:-) and S. enterica ser. Muenster. Analysis of antimicrobial resistance of Salmonella spp. showed that the majority of serovars were fully susceptible to the tested antimicrobials. Only S. enterica ser. Typhimurium and S. enterica ser. Muenster showed a resistance pattern to at least one antimicrobial analyzed. To our knowledge, this study is the first report the prevalence and serovars of Salmonella spp. in free-ranging wild boars in the State of São Paulo, Brazil. Results indicate a low prevalence with variability of Salmonella serovars, with some pattern of antimicrobial resistance. This study highlights the potential role of wild boars as carriers of Salmonella and could pose a risk to wild and domestic animals as well as humans.